DISCURSIVE STRATEGIES OF HISTORICAL TRAUMA: REMEMORY AND THE POETICS OF WITNESS IN TONI MORRISON’S BELOVED - Mardonova Shodiya Shuhratovna (International Journal of Literature and Language Studies, 2026)
Within the broader study of the discursive strategies of African American writers in American literature, this article analyses the neologism “rememory” in Toni Morrison’s Beloved (1987) as a fully developed discursive structure for representing a historical trauma — chattel slavery and the Middle Passage — that resists conventional narration. Where official archives systematically excluded the interior life of the enslaved, Morrison constructs a counter-discourse in which the past is figured as materially persistent, spatially located and bodily inscribed. Integrating trauma theory (Caruth, LaCapra, Herman), cultural-memory studies (Halbwachs, Assmann, Eyerman) and the critical grammar of Hortense Spillers, the study identifies four discursive operations through which rememory functions: the externalization of memory into place; the embodiment of history as corporeal text; ghost discourse as the return of the repressed; and fragmented, non-linear temporality as the formal correlate of traumatic experience. The article concludes that rememory constitutes both a theme and a method, converting the reader from a recipient of information into a participant in a community of witness.